Origin of flooding water through hydrogeochemical identification, the Buenos Aires plain, Argentina - Alconada Magliano, Margarita María (2011)
Hydrogeochemical behaviour of samples of surface and groundwater collected on a cross-section from Mendoza to the Buenos Aires provinces was studied based on chemical trends, mass balance and water mixing. Hydrogeochemical modelling included major, minor elements as well as stable isotopes (deuterium and 18-O). The area investigated is located in the ‘‘Médanos Longitudinales’’ (longitudinal dunes) of the northwest of Buenos Aires province, Argentina. The study area is subject to alternating flooding and drought. Rainfall and surface water subsequently transferred by rivers, canals and lagoons have been usually considered responsible for local flooding. For this study, origins of excess water were investigated using physical and chemical characteristics of the water involved. The prevalence of groundwater inflow to rainfall events was proposed based on data interpretation. Groundwater influence of flows of local and intermediate nature were defined and the importance of recharge, transit and discharge zones was highlighted. Lagoon floodwater, as well as groundwater from observation wells and production boreholes, show components of intermediate origin. Regional recharge water was identified in Mendoza and San Luis provinces. Their discharge zone was inferred to be located beyond the Buenos Aires province.